Nýjar alþjóðlegar leiðbeiningar um endurlífgun - Hjalti Már Björnsson; Davíð O. Arnar (Læknafélag Íslands, Læknafélag Reykjavíkur, 2007)
Hægt er að lesa greinina í heild sinni með því að smella á hlekkinn View/Open Recently the American Heart Association and the European Resuscitation Council published new guidelines for cardiopulmonary resuscitation and emergency cardiovascular care. These new guidelines are the result of extensive review of the scientific literature in this field by The International Liason Committee on Resuscitation. There are some important changes in the new guidelines with a major emphasis on the importance of basic life support, especially chest compressions. The guidelines also promote early defibrillation while the role of pharmacologic therapy during cardiopulmonary resuscitation is not as clear. This article discusses the highlights of the new guidelines.